2013
DOI: 10.1016/j.urolonc.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immediate TRUS rebiopsy in a patient cohort considering active surveillance for favorable risk prostate cancer

Abstract: Introduction and Objective Active surveillance (AS) is an option for the management of favorable risk prostate cancer (CaP) in the PSA era. Published studies have reported variable inclusion criteria for cohort selection. Accurate assessment of individual patient risk in AS is dependent not only upon rigorous selection criteria, but also reliability of diagnosis at tissue biopsy. To date, the impact of immediate transrectal ultrasound (TRUS) rebiopsy in confirming candidates for AS has been incompletely define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A tumour initially assumed to be low risk but was reclassified as a higher risk tumour later may have a worse prognosis if treatment is delayed >1 yr [36]. Based on this information, clinicians adopting AS protocols may wish to perform confirmatory studies earlier rather than later [37,38]. This may especially hold true for patients on AS with more positive biopsy cores and higher PSA density at diagnosis [39].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…A tumour initially assumed to be low risk but was reclassified as a higher risk tumour later may have a worse prognosis if treatment is delayed >1 yr [36]. Based on this information, clinicians adopting AS protocols may wish to perform confirmatory studies earlier rather than later [37,38]. This may especially hold true for patients on AS with more positive biopsy cores and higher PSA density at diagnosis [39].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…While we await clinically applicable and accurate molecular biomarkers, we are dependent on these protocols to help stratify indolent tumors from more aggressive, life‐threatening cancers. Because of concern of underdiagnosis on the initial biopsy, some authors recommend immediate rebiopsy in the form of standard or saturation templates for active surveillance patients . We evaluated the differences in diagnostic accuracy between our departmental standard 12‐core biopsy and an extended saturation biopsy in patients who underwent RP, but would have been candidates for active surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…In studies not using mpMRI, the rate of AS termination after the first confirmatory biopsy was 16%-32%. 4,[18][19][20] Pathologic progression detected by use of mpMRI before the first confirmatory biopsy varied similarly between 14% and 32% in other series. 3,4,7,8 In our study, we showed that the targeted biopsy cores led to more management-changing results than the standard biopsy cores in those patients who had magnetic resonanceeguided biopsies.…”
Section: Commentmentioning
confidence: 55%